Power conversion of renewable energy systems - Fuchs, Ewald F.; Masoum, Mohammad A. S. (New York : Springer, 2011)
Power Conversion of Renewable Energy Systems presents an introduction to conventional energy conversion components and systems, as well as those related to renewable energy. This volume introduces systems first, and then in subsequent chapters describes the components of energy systems in detail. Readers will find examples of renewable and conventional energy and power systems, including energy conversion, variable-speed drives and power electronics, in addition to magnetic devices such as transformers and rotating machines. Applications of PSpice, MATLAB, and Mathematica are also included, along with solutions to over 100 application examples. Power Conversion of Renewable Energy Systems aims to instruct readers how to actively apply the theories discussed within. It would be an ideal volume for researchers, students and engineers working with energy systems and renewable energy. -- Book Description.
Introduction -- Block diagrams of electromechanical systems -- Electric energy sources -- Electronic controllers for feedback systems -- Power electronic converters -- Magnetic circuits : inductors and permanent magnets -- Single-phase, two-winding transformers and autotransformers/variacs -- Three-phase power system and three-phase transformers -- Force and torque production in electromagnetic circuits -- Rotating and linear motion electric machines -- Mechanical loads -- Analyses and designs related to renewable energy systems.
Includes bibliographical references and index.
Keywords: Renewable energy sources; Electric power production